A Bibliometric Analysis of Foreign Direct Investment - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This study aims to systematically map the development of Foreign Direct Investment (FDI) research using a bibliometric approach. Data were collected from the Scopus database covering the period 2000–2026. The analysis employs bibliometric techniques, including co-authorship, citation, keyword co-occurrence, overlay, and density visualization, using VOSviewer to identify research patterns, influential contributors, and thematic evolution within the field. The results show that FDI research has grown significantly and is dominated by key countries such as China, the United States, and India, which act as central hubs in global collaboration networks. Citation analysis reveals that highly influential studies largely focus on the relationship between FDI, economic growth, and environmental sustainability. Furthermore, keyword analysis indicates a shift from traditional economic themes toward more interdisciplinary topics, including renewable energy, carbon emissions, and sustainable development. The overlay and density visualizations confirm that sustainability-related issues are emerging as prominent research areas in recent years. This study contributes by providing a comprehensive overview of the intellectual structure of FDI research, identifying key trends, and highlighting future research directions, particularly in the integration of sustainability, digital transformation, and global policy frameworks.